Perlindungan Yuridis dan Peran Staf Notaris sebagai Saksi dalam Akta - Eka Ratna Putri; Benny Djaja; Maman Sudirman (Majelis: Jurnal Hukum Indonesia, 2025)
The making of authentic deeds by a notary is part of the legal service that has the highest evidentiary value in the Indonesian civil law system. One of the formal requirements of an authentic deed according to Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary (UUJN) is the presence of two witnesses who know and directly witness the process of signing the deed. In notarial practice, notary staff are often appointed as witnesses for reasons of administrative convenience, trust, and availability of time. This study aims to examine the legal position and role of notary staff as witnesses in authentic deeds and the form of legal protection available if the deed is legally disputed. The research method used is normative legal with a statutory and conceptual approach, supported by literature studies and analysis of related court decisions. The results of the study indicate that notary staff are legally valid as witnesses as long as they meet the requirements as competent witnesses according to law. However, if a dispute arises over the deed, the staff can be asked for information as a witness in court and has the potential to face legal pressure. Therefore, legal protection for notary staff includes the principle of good faith, legal protection for witnesses, the right to legal assistance, and the ethical responsibility of notaries as employers. In conclusion, there needs to be more explicit regulations regarding the role of staff in deeds and clear protection mechanisms to maintain professionalism, integrity, and legal certainty in notarial practice.